Menumbuhkan Semangat Kreativitas Dan Rasa Percaya Diri Anak Melalui Kebebasan Mewarnai - Mentari Septanya Sitorus; Jusbaeni Jusbaeni; Firnawati Firnawati; Indah Nur Afiah; Nahridzah Mahjubuh Shiber (ABDIMASY: Jurnal Pengabdian Kepada Masyarakat, 2026)
The early years of childhood are a time when imagination is at its peak, yet the use of colouring activities in educational institutions often remains dictatorial and limits children's expression. This community service programme aims to provide creative stimulation to strengthen children's creativity, fine motor skills, and independence through a liberating approach. The implementation method combines a participatory approach and an inclusive humanistic pedagogy, in which children are given full authority to express themselves through four main stages: orientation to affection, exploration of tools, scaffolding, and reflection and appreciation. Observasi menunjukkan transformasi perilaku dan keterampilan yang signifikan pada tiga domain utama. In the sensorimotor domain, there was an increase in hand-eye coordination in the 4-6 age group and an improvement in the use of gradation techniques in the 7-10 age group. In the cognitive-creative domain, children demonstrated courage in expressing themselves symbolically through the use of unconventional colour palettes to represent their moods. In the psychosocial domain, there was an increase in independence and self-confidence, as evidenced by the children's ability to make decisions without constant validation from adults, as well as their courage to present their work in public. The conclusion of this activity is that a humanistic and liberating art approach is effective in stimulating intrinsic motivation, optimising fine motor skills, and building children's independent character in the long term